2016
DOI: 10.3168/jds.2015-9596
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental relationships of detailed milk fatty acids profile determined by gas chromatography in Brown Swiss cows

Abstract: The aim of this study was to characterize the profile of 47 fatty acids, including conjugated linoleic acid (CLA), 13 fatty acid groups, and 5 Δ(9)-desaturation indices in milk samples from Brown Swiss cows. The genetic variation was assessed and the statistical relevance of the genetic background for each trait was evaluated using the Bayes factor test. The additive genetic, herd-date, and residual relationships were also estimated among all single fatty acids and groups of fatty acids. Individual milk sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
44
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 67 publications
16
44
0
Order By: Relevance
“…Moreover, it should be remembered that only one record per animal was available. This condition, which undoubtedly reduces the reliability of the measure, is rather frequent in studies on FA genetic parameter estimation using FA_GC also in cattle (e.g., Stoop et al, 2008;Mele et al, 2009;Pegolo et al, 2016). On the other hand, the recording of a single measure per animal is more representative of the practical situation of a breeding scheme where innovative phenotypes are considered among the selec-tion goals.…”
Section: Genetic Parameters Of Milk Fa Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be remembered that only one record per animal was available. This condition, which undoubtedly reduces the reliability of the measure, is rather frequent in studies on FA genetic parameter estimation using FA_GC also in cattle (e.g., Stoop et al, 2008;Mele et al, 2009;Pegolo et al, 2016). On the other hand, the recording of a single measure per animal is more representative of the practical situation of a breeding scheme where innovative phenotypes are considered among the selec-tion goals.…”
Section: Genetic Parameters Of Milk Fa Profilementioning
confidence: 99%
“…Ruminant dairy products are among the most important sources of CLA in human diets (Nudda et al, 2014). Although animal feeding is considered the most important factor affecting milk fatty acid (FA) composition (Cabiddu et al, 2005;Sánchez et al, 2010), genetic variation for these traits has been reported in cattle (Stoop et al, 2008;Pegolo et al, 2016) and sheep (Sánchez et al, 2010;Correddu et al, 2018), suggesting the possibility for a genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Rico [30] also found this FA to be positively correlated with EME. Although not highly correlated with de novo FAs, iso-palmitic acid is positively correlated with other branched-chain FAs, often of microbial origin, and negatively correlated with linoleic acid [31].…”
Section: Informative Fatty Acidsmentioning
confidence: 84%
“…the ratio between casein and total protein) (15.1%), lactose (17.0%) and urea (35.6%) were much more heritable at both the experimental and population levels. The estimated heritabilities of the detailed fatty acid profile of the milk samples were in the same range as those of the PC of the volatile fingerprint of cheeses obtained from the same milk, with the exception of the saturated odd-numbered fatty acids and a few others [40]. A possible explanation for such similar ranges of heritabilities could be related to the origin of the VOC, since many molecules may be produced from milk fat via different biosynthetic pathways [3].…”
Section: Resultsmentioning
confidence: 99%